HUBUNGAN DUKUNGAN KELUARGA DENGAN KUALITAS HIDUP LANJUT USIA PENDERITA HIPERTENSI DI DESA MUHAJIRIN DAN DESA GOTALAMO KECAMATAN MOROTAI SELATAN - Khofria Nurzamzamni Kharie; Juwita Moreen Toar; Lenny Gannika (JURNAL KEPERAWATAN, 2022)
Abstract Background. Hypertension is a non-communicable disease that is a serious health problem in the elderly today. The way to control hypertension in the elderly is to change their lifestyle and control their health, where in carrying out lifestyle changes and controlling the health of the elderly family support is needed. Purpose of this study was to determine the relationship between family support and the quality of life of elderly people with hypertension in Muhajirin village and Gotalamo village, South Morotai District. Method in this research is associative quantitative research design with a cross sectional approach. The sampling technique used is total sampling with a sampling of 30 respondents. Results of the study based on the chi-square test carried out showed that pâ‰¤0.000 where the result was smaller than p (0.05) so that Ho was rejected and Ha accepted. Conclusion there is a relationship between family support and the quality of life of the elderly with hypertension in Muhajirin Village and Gotalamo Village, South Morotai District, Morotai Island Regency.